Assessment of post harvest loss of wet fish: a novel approach based on sensory indicator assessment (SAARC Journal of Agriculture, 2015)
As a very common feature of fish marketing, small-scale fisheries in tropical countries suffers from huge post-harvest loss every year. A method was proposed to quantify the post-harvest quality loss of wet fish using sensory based assessment tool. The assessments were conducted on four fish species (rohu Labeo rohita; Ilish Tenualosa ilisha, catfish Pangasius sutchi and tilapia Oreochromis niloticus) in different steps of major distribution channels in Bangladesh for a year. Sensory quality defect point data were standardized with corresponding biochemical and microbiological quality parameters through interval estimate based on regression analysis, where a near to actual sensory quality breaking point was found to be DP 3.3. High value of goodness of fit 2 R indicated a highly fitted regression model for all the fishes tested, with highly significant (p